Specific features of elite bodybuilders' training process in competition period - A.A. Tihorsky (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: To substantiate methodic of training process construction for elite bodybuilders in competition period with usage of different training methods. Material: elite bodybuilders - members of combined team of Ukraine (n=16) participated in the research. Results: we presented comparative characteristic of the most often used bodybuilding training methodic. Besides, optimal training methodic in competition period was worked out and substantiated. Such methodic permits to improve body proportions at the account of fat layer reduction. By the data of Harvard step-test the sportsmen improved organism's functional potentials by 6%. Conclusions: the offered methodic noticeably reduces probability of functional unfavorable states (over-training, overloading, traumas). The methodic permits to achieve the required sport form without over-tension adaptation-compensatory mechanisms and acquire maximal muscular relief; improve proportions with minimal losses of muscles' volume.